Language and Education: A new look at communicability between the deaf and hearing from the philosophical Hermeneutical perspective of H.-G. Gadamer (Research, Society and Development, 2023)
This research sought to carry out a study on the relationship between language and education and its implications for the communicability of deaf and hearing people based on the works “Truth and Method I” and “Truth and Method II” by Hans-Georg Gadamer. The objective of the research is to establish a new horizon of communication between deaf and hearing people based on Gadamerian theory, in order to contribute to the education and inclusion of deaf individuals in school and society. The development of the work was divided into 6 topics. In the first 4 topics, issues related to the deaf subject were addressed, with the aim of informing the reader about the peculiarities that involve this subject, such as their identity, culture, mother tongue, as well as some notes on special education and school inclusion. In the fifth and sixth topics, Gadamerian theory was discussed from a hermeneutic philosophical perspective of language. To this end, the bibliographical research method was used, through the works of Gadamer and commentators of this main author of philosophical hermeneutics. It was possible to relate the themes of education and language with the education of deaf people, as well as establishing a new perspective on communicability between deaf and hearing people in search of a common horizon of understanding. It was concluded that it is possible to establish communicability between deaf and hearing people, not based on their differences, but on their identity. Hermeneutics, as the art of interpreting and understanding, presents us through language with various possibilities of communication and understanding, requiring us to think about our prejudices, overcome our fears in order to seek the other exactly as he is, that is, a human like us.